Membedah Syirik : Bahaya Tersembunyi Yang Mengancam Umat Manusia - Arimbi Pramesty; Audyni Khalisyah; Delima Delima; Farah Madina; Fitria Mayasari; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Shirk, the sin of associating partners with Allah, poses a significant threat to the foundation of faith among Muslims. In the Qur'an, shirk is described as the greatest sin that will not be forgiven except through sincere repentance. This article aims to explore the concept of shirk, define its various forms, and provide examples of major (akbar) and minor (ashgar) shirk. Using a qualitative approach, this research analyzes Islamic literature and Qur'anic verses to examine the impact of shirk on the spiritual and moral lives of Muslims. The findings indicate that shirk can damage an individual's relationship with Allah and threaten moral integrity. In modern contexts, shirk may also manifest in subtle forms, such as materialism. Education on Tawhid, emphasizing the oneness of Allah, is crucial in preventing shirk. This study seeks to raise awareness about the dangers of shirk and the importance of maintaining pure faith. With a better understanding of shirk, it is hoped that individuals can avoid such practices and align their lives with Islamic teachings.